2022
DOI: 10.7759/cureus.21552
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Bradyarrhythmias: A Case Report With Literature Review

Abstract: We report a case of a 51-year-old male with no past medical history who was admitted for acute hypoxic respiratory failure secondary to COVID-19. During his hospitalization, the patient developed sinus bradycardia and frequent sinus pauses were observed on telemetry. No other cause of his bradyarrhythmia was identified except for his COVID-19 infection. There has been numerous case reports and case series describing different arrhythmias seen in patients infected with COVID-19. We present a case of sinus arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In patients with hemodynamically stable SA, the consideration of additional pacemaker therapy is warranted in patients with overt symptomatic SA [8]. Te efcacy of permanent pacemaker implantation in improving SA in patients with COVID-19 infection has been described in some reports [22][23][24][25], while the utilization of temporary pacemakers has also been reported [4,26]. However, in this case, due to the patient's long-term impairment of consciousness, even if the SA episode presented with symptoms, she was unable to articulate them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with hemodynamically stable SA, the consideration of additional pacemaker therapy is warranted in patients with overt symptomatic SA [8]. Te efcacy of permanent pacemaker implantation in improving SA in patients with COVID-19 infection has been described in some reports [22][23][24][25], while the utilization of temporary pacemakers has also been reported [4,26]. However, in this case, due to the patient's long-term impairment of consciousness, even if the SA episode presented with symptoms, she was unable to articulate them.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the duration of SA in our patient, from onset to disappearance (14 days), was comparable to that observed in these two cases. Ansari et al [ 4 ] demonstrated that the average age of COVID-19 patients with bradyarrhythmia was 56.3 ± 15.2 years old. Although there have been reports of transient SA in patients as young as 83 years old [ 18 ], the majority of cases have been observed in younger individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision was made based on the identification of COVID-19 as a transient trigger. In contrast, permanent pacemakers have been placed in some COVID-19 patients presenting with or without syncope (10)(11)(12). In patients with more than one type of bradyarrhythmia, such as complete heart block, sinus bradycardia, sinus arrest, second-degree atrioventricular (AV) block, or high AV block, 30% eventually required a permanent pacemaker (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of the global COVID-19 pandemic, medical professionals have been faced with an ever-evolving landscape of symptoms and complications associated with the Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus [1]. While respiratory distress and pneumonia have been at the forefront of clinical attention, it has become increasingly evident that COVID-19 can affect multiple organ systems, leading to a wide array of clinical manifestations [2][3][4][5]. One such manifestation that has emerged as an intriguing and potentially life-threatening complication is bradycardia, a condition characterized by an abnormally slow heart rate.…”
Section: Introductionmentioning
confidence: 99%